Analysis and simulation of evacuation routes during disaster situations: a case study in Kuala Lumpur City (KLC) - Ng, Choy Peng; Ahmad, Nordila; Wong, Mohd Muhaimin Ridwan; Law, Teik Hua; Zul Bahari, Ahmad Najman ‘Azam; Mohd Rofi, Muhamad Faisharulfaizi; Abas, Fuad (National University of Malaysia, 2025)
Kuala Lumpur City (KLC) is susceptible to disasters because of its large population, crucial infrastructure, and vital economy. In this study, we used the disaster risk maps generated for fl ash floods and landslide hazards in KLC to identify key areas for humanitarian assistance and disaster relief (HADR) activities. We employed analysis and simulations to determine the most effective evacuation routes from key areas to crucial HADR centres, including medical facilities, police stations, fi re stations, and temporary evacuation centres, during a disaster. We conducted the investigation by considering factors like evacuation time, route accessibility, and overall efficiency. We proposed multiple routes during the disaster scenario, including the use of alternative roads with reduced capacity if the major roads became inaccessible. This case study highlights the significance of ongoing evaluation and improvement of evacuation preparations. The measures, including the use of cutting-edge traffic management systems, frequent practice sessions and instruction for emergency responders, and heightened public awareness and preparedness initiatives, could potentially improve evacuation time. By implementing these strategies, KLC may enhance its ability to withstand and respond to disaster scenarios, thereby safeguarding lives and mitigating the potential consequences of disasters. The results of this study could provide useful insights for Kuala Lumpur City Hall to plan evacuation routes during a disaster.